Structural parameters in the formation of omnidirectional high reflectors - Singh S.K.; Pandey J.P.; Thapa K.B.; Ojha S.P. (My University, 2025)
We investigate the structural parameters for the formation of omnidirectional photonic band gap in one dimensional photonic crystal. Simple transfer matrix method is used for calculations. The effect of two parameters, namely, refractive index contrast and filling fraction on omnidirectional reflection is investigated. We find from our study that when nL, ni ns and d are fixed, omnidirectional bandgap increases with increasing hH/nL i.e., with increasing nH. Therefore, omnidirectional bandgap can be increased by using the material of high refractive index nH when the low index material nL is fixed. We also find that for the considered system of Si-SiO2, omnidirectional reflection range increases with filling fraction, goes to a maximum value and finally comes to zero. The maximum value of the omnidirectional reflection range is obtained at a value of 0.29 of the filling fraction. The range for allowable values of refractive index of ambient medium (ni) has also been estimated.